1981
DOI: 10.1073/pnas.78.12.7327
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interferon-mediated induction of indoleamine 2,3-dioxygenase in mouse lung by inhibitors of prostaglandin biosynthesis.

Abstract: Inhibitors of fatty acid cyclooxygenase such as indomethacin (0.1 mM), phenylbutazone (0.3 mM), and aspirin (1 mM) were found to suppress almost completely the interferonmediated induction ofindoleamine 2,3-dioxygenase in mouse lung slices. However, phenacetin, an anti-inflammatory agent devoid ofcyclooxygenase inhibitory activity, and sodium salicylate, a weak inhibitor ofcyclooxygenase, were much less active under identical conditions. Glucocorticoids including dexamethasone, betamethasone, and cortisone, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 26 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…For example, early studies in mouse lung slices treated with IFNγ reported that COX inhibitors (aspirin and indomethacin) inhibited IDO1 induction [97]. Subsequent studies indicate an important role for COX2-derived PGE 2 in elevating IDO1 in different tumour cells (e.g.…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 98%
“…For example, early studies in mouse lung slices treated with IFNγ reported that COX inhibitors (aspirin and indomethacin) inhibited IDO1 induction [97]. Subsequent studies indicate an important role for COX2-derived PGE 2 in elevating IDO1 in different tumour cells (e.g.…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 98%
“…207 Induction of IDO can also be blocked in vitro by cyclooxygenase 2 inhibitors. 212 When murine breast cancer vaccine recipients received the oral cyclooxygenase 2 inhibitor celecoxib, an increase in tumor-specific CTLs was observed. 35 Trophoblast invasion and spiral artery remodeling are tightly controlled processes, likely kept in check both by molecular programming of trophoblast cells and by paracrine immune factors.…”
mentioning
confidence: 99%
“…The first evidence for a role of IDO in immune regulation was observed when IDO expression was induced following viral infection or treatment with interferon (IFNγ), an important inflammatory cytokine (Yoshida et al, 1979;Yoshida et al, 1981). A prior observation that IDO is present in the urine of cancer patients then re-surfaced and its importance reevaluated (Rose, 1967).…”
Section: Ido In the Immune Systemmentioning
confidence: 99%
“…Another recent study has revealed that the cytotoxic agent β-lapachone is a direct inhibitor of IDO, postulating that this cytotoxic agent may benefit from the additional immunological effects that derive from its potent uncompetitive inhibitory effects on IDO1 activity. Other drugs in use include NSAIDs that indirectly block IDO activity as a result of COX2 inhibition (Sayama et al, 1981). Another effective IDO inhibitor in mouse studies is the anti-inflammatory ethyl pyruvate, which by inhibiting NF-kB activity blocks IDO expression and produces robust anti-tumor responses that are both T cell and IDO dependent (Muller et al, 2010).…”
Section: Clinical Trials Of Ido Inhibitorsmentioning
confidence: 99%